General overview to enterprise risk management with its key components and determinants from the management perspectives - (:unkn) unknown (IGI Global, 2019)
Enterprise Risk Management (ERM) is a comprehensive and holistic approach to risk management, requiring the determination, assessment and management of risks in an integrated and systematic manner. ERM has been considered as a financial, and accounting-based tool used to assess and manage the risks an organisation faces and to meet the compliance requirements of creditors, rating agencies, regulators and stock exchanges. Although ERM is widely examined by internal audit and finance scholars, ERM researches from management and strategy perspectives are limited in the literature. The purpose of this chapter is to provide a comprehensive overview of ERM including ERM concepts and definition of the risks and categorisation of risks surrounding the organisations. Moreover, the chapter handles how the risk management evolved into ERM. The distinguishing components of ERM (pillars) and the leading factors and motivation for ERM adoption (determinants) are presented. © 2020 by IGI Global. All Rights reserved.